Understanding gender-differentiated constraints to farm household investments in adolescents: Implications for their nutritional status - Bouis, Howarth E.; Palabrica-Costello, Marilou; Solon, Orville; Limbo, Azucena B. (International Center for Research on Women, 1994)
The nutrition, health, education, and contributions to family income of adolescents from farm households residing in a southern Philippine province are studied in this report. The primary objective of the analysis is to provide an understanding of a household resource allocation process that relies on adolescents for income generation on the one hand, but that must provide resources for their nutrition, health, and education on the other hand. The study is based on three sources of information: (i) a series of four household surveys of 448 families conducted in 1984/85, (ii) one follow-up survey round conducted in 1992 of households that had been previously surveyed, and (iii) an ethnographic study consisting of in-depth, more flexible interviews in 1992 of a subset of nineteen carefully selected households from the 1984/85 surveys. An analysis of the intra-household distribution of food indicates that preschoolers are favored. Even though other age and gender groups consume diets that are less-preferred (in a non-nutrient sense), they are compensated by greater proportions of less preferred foods. Consequently, nutrients were relatively evenly distributed among various age and gender groups. The findings of the ethnographic study corroborate these conclusions closely. Parents express repugnance at the suggestion that males should be entitled to better food than females, or that family members that earn more should be entitled to better food.